Ankle sprain: pathophysiology, predisposing factors, and management strategies - Tricia J Hubbard; Erik A Wikstrom (Dove Medical Press, 2010)
Tricia J Hubbard, Erik A WikstromUNC Charlotte, Department of Kinesiology, CharlotteAbstract: With the high percentage (up to 75%) of initial lateral ankle sprains (LAS) leading to repetitive sprains and chronic symptoms, it is imperative to better understand how best to treat and rehabilitate LAS events. The purpose of this paper is to review LAS pathophysiology, predisposing factors, and the current evidence regarding therapeutic modalities and exercises used in the treatment of LAS. Functional rehabilitation, early mobilization with support, is the current standard of care for LAS. However, the high percentage of reinjury occurrence and development of chronic symptoms (up to 75%) after a LAS, suggests the current standard of care may not be effective. Recent evidence has shown the need for more stringent immobilization to facilitate ligament healing and restoration of joint stability and function after a LAS. Additionally, the importance of adding adjunctive therapies, specifically joint mobilizations and balance training have been shown to improve function and decrease the incidence of reinjury after a LAS. Modifying current rehabilitation protocols to include protecting the ankle joint with stringent immobilization, and including joint mobilizations and balance training may be the first step to decreasing the incidence of short and long term ankle joint dysfunction.Keywords: rehabilitation, recurrent sprains, chronic ankle instability (CAI)